Demo Masak Kudapan Lokal Pada Orang Tua dengan Anak Usia Sekolah di Desa Sepabatu: Local Snack Cooking Demonstration for Parents with School Age Children at Sepabatu Village - Taufik, Erviana (Journal of Community Engagement in Nursing, 2024)
ABSTRACT (12 pt, bold) Children experience rapid physical, intelligent, mental and emotional growth. Food that contains nutritional elements is very necessary for the growth and development process. Children will be able to develop their potential to the maximum if supported by good nutrition. This requires the mother's role in providing snacks for the child. This service activity aims to provide knowledge for mothers who have school-aged children in providing local snack dishes that are rich in nutrition. The method of implementing the service uses education, cooking demonstrations, and mentoring. Community service partners are housewives who have school-age children at SDN 016 Tandung, Sepabatu Village. The results of the service show that this activity increases mothers' knowledge about healthy food and how to make healthy local snacks for school-age children. The conclusion of this service activity is that there has been an increase in the knowledge of housewives with school-age children at SDN 016 Sepabatu Village about healthy snacks and how to cook nutritious local snacks. Keywords: Cooking demonstration, Local Snacks, Parents, School Age.